Chromium Induced Elevated Glutathione S-transferase Activity in Cirrhina mrigala: Response of GST activity in fish - Gull, Samreen; Abdullah, Sajid; Naz, Huma; Abbas, Khalid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
In aquatic bodies, heavy metals contamination is a most important issue all over the world. Heavy metals are persistence in nature and can store in aquatic environment. These metals have ability to induce oxidative stress and altered the enzymes activities. Therefore, in current investigation the activity of glutathione S-tranferase (GST) in hepatic, renal and cardiac tissues of fish, Cirrhina mrigala under various sub-lethal concentrations (1/3rd, 1/4th and 1/5th of LC50) of chromium (Cr) was evaluated. The fish was exposed to chromium for 21-day and sampling was done on weekly basis. Results demonstrated that the GST activity was significantly augmented in hepatic, renal and cardiac tissues of exposed fish in relation to control. Comparison among organs revealed that the maximum GST activity was observed in hepatic tissues of fish followed by renal and cardiac tissues. The GST activity gradually augmented with increasing the concentration and duration of exposure. In conclusion, the use of GST enzyme as biomarkers is not a new approach but can be used successfully to assess the toxicity associated with metals in aquatic animals.